“The Magic of the Meeting Necessitates Having Multiple Voices Heard.” An Interview with François Cooren about Ventriloquism, Interaction, and the Montreal School - Haug, Christoph (Communiquer, 2020)
This interview with François Cooren, professor in the Department of Communication at the Université de Montréal, discusses his best-known contribution to communication theory, his metaphor of communication as ventriloquism. According to this perspective, we all have a “capacity to make other beings say or do things while we speak, write, or, more generally, conduct ourselves” (Cooren, 2012, p. 4). More specifically, the notion of “meetings” and the contribution of ventriloquism to their studies are at the core of this interview. Initially, this interview was conducted by email in the fall of 2019 for a community of meeting researchers and meeting professionals, and then slightly edited for the present publication.